Persaingan industri ride-hailing di Indonesia: Peran country of origin, perceived quality, dan brand credibility terhadap purchase intention - Alfy, Riadh; Hurriyati, Ratih; Widjajanta, Bambang (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2024)
This study examines the influence of country of origin on purchase intention, mediated by perceived quality and brand credibility among consumers of ride-hailing services in Indonesia. Conducted using a descriptive quantitative approach via Google Forms survey, data analysis utilized the SEM-PLS method with SmartPLS 3.0 software. Findings reveal positive and significant effects of country of origin and brand credibility on purchase intention. However, perceived quality does not significantly influence purchase intention. Brand credibility mediates the relationship between country of origin and purchase intention, while perceived quality does not. The gap between findings and concepts presents a limitation for researchers but offers opportunities for future analysis. This research contributes a fresh perspective on the impact of country of origin on purchase intention among Indonesian ride-hailing consumers.